Protective Layered Model of a Multi-Component Architectural-Composite Structure of an Optoelectronic Information Leakage Channel - Dzyanyi, Nazarii (Social Development and Security, 2025)
Purpose. Development of a protective model of a multi-component architectural-composite structure of an optoelectronic information leakage channel, which, unlike existing approaches, takes into account the complex interaction of layered elements and allows for a more accurate assessment and minimization of the risks of speech information leakage. Method. Theoretical generalization and practical modeling based on the results of previous empirical studies. Findings. А protective model of a multi-component architecturally-composed structure of an optoelectronic information leakage channel has been constructed, which takes into account the combination of layered elements, the response from the passage of a laser beam into the interior of the premises and in the opposite direction, and is deployed at the level of an aggregate and complex model. A mathematical model has been developed that describes the minimization of information loss through the optoelectronic information leakage channel from the Laser Acoustic Reconnaissance Systems, allowing to determine the optimal amount of risk reduction for each hypothetical layer of the source material, which, in turn, corresponds to the maximum degree of security of the premises. Theoretical implications. The study develops the theoretical foundations of information protection by proposing a complex model of the optoelectronic leakage channel, which takes into account the complex processes of interaction of laser radiation with multilayer structures. Practical implications. The research provides a scientific basis for the design and optimization of protective systems, allowing to achieve the most effective counteraction to laser acoustic reconnaissance systems by targeted influence on the physical properties of multilayer architectural components. The results of the research can be used to modernize existing information protection systems, for example, by developing new types of protective films or coatings for windows. Value. The study demonstrates that the developed model and the obtained results can be used to create more effective protection tools, which will contribute to increasing the security of information systems and objects and stimulate further interdisciplinary research in this important field.